Generation of functional ciliated cholangiocytes from human pluripotent stem cells - Mina Ogawa (Nature Portfolio, 2021)
Current protocols to generate cholangiocytes from human pluripotent cells produce immature cells. Here the authors identify retinoic acid, BMP, cAMP and Rho kinase pathways as regulators of cholangiocyte maturation, and generate ciliated cholangiocytes expressing high levels of CFTR that form ductal structures in vivo.